2012
DOI: 10.5194/acp-12-4387-2012
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of meteoric smoke particles with sulphuric acid in the Earth's stratosphere

Abstract: Abstract. Nano-sized meteoric smoke particles (MSPs) with iron-magnesium silicate compositions, formed in the upper mesosphere as a result of meteoric ablation, may remove sulphuric acid from the gas-phase above 40 km and may also affect the composition and behaviour of supercooled H 2 SO 4 -H 2 O droplets in the global stratospheric aerosol (Junge) layer.This study describes a time-resolved spectroscopic analysis of the evolution of the ferric (Fe 3+ ) ion originating from amorphous ferrous (Fe 2+ )-based sil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 55 publications
(83 reference statements)
3
60
0
Order By: Relevance
“…The overpredicted nucleation rate in these volcanically quiescent conditions may be a result of gas phase concentrations of H 2 SO 4 being too high in the model. Possible explanations might be that the model does not include the sink for gas phase H 2 SO 4 provided by meteoric debris, shown to be important by Saunders et al (2012) and Brühl et al (2013) or underestimated H 2 SO 4 photolysis rates in our simulations.…”
Section: Particle Size Distributionmentioning
confidence: 95%
“…The overpredicted nucleation rate in these volcanically quiescent conditions may be a result of gas phase concentrations of H 2 SO 4 being too high in the model. Possible explanations might be that the model does not include the sink for gas phase H 2 SO 4 provided by meteoric debris, shown to be important by Saunders et al (2012) and Brühl et al (2013) or underestimated H 2 SO 4 photolysis rates in our simulations.…”
Section: Particle Size Distributionmentioning
confidence: 95%
“…Bluhm et al (2010) demonstrated that phytoplankton can reduce IO − 3 to I − , while UV light can also drive the reduction of IO − 3 to I − in seawater (Saunders et al, 2012b;Wong, 1991). Doubts remain regarding iodine inorganic speciation in aerosols and which factors are able to control this speciation ; UV light and ozone have been proposed to play important roles (Saunders et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…These particles are present in sufficient quantities (∼1000's per cm 3 [4]) to play a significant role in a number of atmospheric processes, including cloud nucleation and removal of H 2 SO 4 from the gas phase at high altitude. Laboratory dissolution studies using analogue ANPs provide the physical constraints necessary to assess their environmental impact via modelling [7]. Similarly in astrophysics, Mg-rich pyroxene ANPs condense as dust particles (along with other solid species) in the circumstellar regions surrounding evolved stars and are ubiquitous throughout space.…”
Section: Introductionmentioning
confidence: 99%